Model of Academic Risk Management of Educational Institutes Under the Office of Primary Educational Service Area - ถาจ พระดารา อคฺคญฺญาโณ; ศิริวรรณ อินถา; บุดดาวงษ์ พระมหาญาณวัฒน์ ฐิตวฑฺฒโน (Journal of Educational Review Faculty of Education in MCU, 2018)
The objectives of this dissertation were; 1) to study the state of academic risk management of educational institutes under the Office of Primary Educational Service Area, 2) to develop a model of academic risk management of educational institutes under the Office of Primary Educational Service Area, and 3) to propose a model of academic risk management of educational institutes under the Office of Primary Educational Service Area. The mixed research methodology was used in the study as follows; 1) to collect the information from documents and analyze by content analysis, 2) to collect the data by questionnaires from 367 samples consisting of school administrators and teachers, and then analyze by frequency, mean, percentage, and standard deviation, 3) to interview with 8 experts and analyze by content analysis, and 4) to conduct a focus group discussion with 10 experts for the finalized model of academic risk management. The research results showed that: 1. The state of academic risk management of educational institutes under the Office of Primary Educational Service Area was at the moderate level overall. In details, the highest level was on measurement and evaluation, followed by media innovation and information technology development, curriculum development, and teaching and learning management respectively. The risks in each aspect were on strategic plan, operation, budget spending, and performance under regulations. 2. There were 8 steps in developing the academic risk management of educational institutes under the Office of Primary Educational Service Area; 1) Internal Environment, 2) Objective Setting, 3) Event Identification, 4) Risk Assessment, 5) Risk Responses, 6) Control Activities, 7) Information and Communication, and 8) Monitoring. 3. Five operation models approved by the experts were as follows; 1) The state of academic risk management of educational institutes consisted of (1) curriculum, (2) teaching and learning, (3) media innovation and information technology development, and (4) measurement and evaluation. 2) The objectives of academic risk management of educational institutes consisted of (1) to set up activities reducing risks, (2) to enhance the role of school personnel in risk management, and (3) to improve the school academic management system. 3) Four risk indicators were financial risk, strategic risk, operation risk, and rules and regulations risk. 4) Participatory risk management was composed of (1) to set strategic plans for academic, action plan and project, and activity, (2) to produce information, action plan, implementation method, rules and regulations, and publicize in school, (3) to follow the academic plan, (4) to follow up, monitor, report, adjust and improve the plan regularly, and (5) to arrange a meeting with sub-unit administrators for acknowledgement, consideration and reflection. 5) Risk control activity and monitoring consisted of (1) regular follow up and monitor, (2) improving performance skills of the personnel, and (3) meeting, reporting and reflecting in the time frame.